Renewable energy futuristic approaches - Thomson, George (Callisto Reference, 2015)
Renewable energy is an important and fundamental step towards sustainable energy by optimizing the utilization of renewable energy sources, such as hydroelectricity, solar energy, wind energy, wave power, geothermal energy and tidal power. Renewable energy is an area of concern in our daily life, and also a very important topic for scientific researches. Endless number of researches and studies are going on day-in and day-out on renewable energy. This book is useful for scientists, researchers, students and anyone else willing to delve deeper into the field of renewable energy.